Advanced low-thermal fortification strategy for dill juice: enhanced bioaccessibility and functional properties through MLP-RSM optimization - Yıkmış, Seydi; Duman Altan, Aylin; Demirel, Selinay; Türkol, Melikenur; Tokatlı, Nazlı; Tokatlı Demirok, Nazan; Aljobair, Moneera O.; Karrar, Emad; Mohamed Ahmed, Isam A. (Frontiers in Nutrition, 2025)
In this study, a combination of ultrasound and microwave technologies (USMW) was applied to increase the functional properties of Anethum graveolens L. (dill) juice and the obtained samples were comprehensively evaluated in terms of biofunctionality. Total phenolic content (TPC), β-carotene, total chlorophyll, antioxidant capacity (FRAP) and antidiabetic enzyme inhibition (α-glucosidase, α-amylase) were determined. The optimum process parameters were successfully estimated by Response Surface Methodology (RSM) and Multilayer Perceptron (MLP) models. USMW process increased the extraction of phenolic compounds and carotenoids, providing significant increases in TPC (126.08 mg GAE/100 mL), β-carotene (42.82 mg/100 mL) and chlorophyll (4.42 g/100 mL) levels (*p < 0.05). In the simulated post-digestion bioavailability assessments, the ultrasound and microwave (DJ-USMW) group showed the highest recovery rates. In addition, potential antidiabetic effects were confirmed by the inhibition of α-glucosidase (61.65%) and α-amylase (53.11%). PCA and clustering analyses showed that USMW application significantly separated the samples. The obtained results demonstrate that USMW technology is a sustainable and effective method, especially for the development of functional beverages, as an alternative to traditional heat treatments.